2019
DOI: 10.1007/s00253-019-09694-2
|View full text |Cite
|
Sign up to set email alerts
|

High titer MVA and influenza A virus production using a hybrid fed-batch/perfusion strategy with an ATF system

Abstract: A cultivation strategy to increase the productivity of Modified Vaccinia Ankara (MVA) virus in high-cell density processes is presented. Based on an approach developed in shake flask cultures, this strategy was established in benchtop bioreactors, comprising the growth of suspension AGE1.CR.pIX cells to high cell densities in a chemically defined medium before infection with the MVA-CR19 virus strain. First, a perfusion regime was established to optimize the cell growth phase. Second, a fed-batch regime was ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 49 publications
(101 reference statements)
5
55
0
Order By: Relevance
“…Similar doubling times and high viabilities before infection were also observed for the cell growth phase in the present study comparing an acoustic settler with different recirculation strategies and an ATF system. Furthermore, the t d values obtained with the acoustic settler in this study were in agreement with values reported previously for AGE1.CR.pIX cells cultivated in perfusion mode with an ATF system operated at higher exchange rates (between 28 and 41 h) Vazquez-Ramirez et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar doubling times and high viabilities before infection were also observed for the cell growth phase in the present study comparing an acoustic settler with different recirculation strategies and an ATF system. Furthermore, the t d values obtained with the acoustic settler in this study were in agreement with values reported previously for AGE1.CR.pIX cells cultivated in perfusion mode with an ATF system operated at higher exchange rates (between 28 and 41 h) Vazquez-Ramirez et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…1A) with a polyethersulfone (PES) hollow fiber membrane (0.2 μm pore size, 470 cm 2 , 76 fibers with 0.9 mm diameter, Spectrum). The recirculation exchange flow rate was decreased from 1.0 to 0.8 L/min compared with previous studies (Genzel et al 2014;Vazquez-Ramirez et al 2019) to ensure a laminar flow regime in the membranes (see "Hydrodynamic stress" section). (2) An acoustic settler (10 L acoustic chamber version, SonoSep Technologies) ( Fig.…”
Section: Perfusion Cell Culturementioning
confidence: 99%
See 3 more Smart Citations